(untitled) (Research, Society and Development, 2025)
Dengue virus (DENV) is an arbovirus transmitted by the bite of the female Aedes aegypti mosquito and has four serotypes (DENV-1, DENV-2, DENV-3, and DENV-4). Dengue can progress to an asymptomatic form, a classic form with fever and myalgia, or a severe hemorrhagic form. In pediatrics, dengue is difficult to diagnose because it is a nonspecific febrile syndrome. The objective of this study is to present an epidemiological analysis of dengue cases in children in the Paraíba Valley. A primary epidemiological study was conducted, using direct documentary sources from TABNET, quantitative in nature, and supported by a secondary literature review. Dengue cases from 2014 to 2023 in the Paraíba Valley and mountainous regions were analyzed, in the pediatric age group from 0 to 14 years. The months with the highest incidence of the disease were: April with 3,095 cases, followed by March with 2,175 and May with 2,109. Therefore, the incidence was highest in the fall, accounting for approximately 60% of cases, followed by summer, corresponding to 31.08%. Analyzing the cities of the Paraíba Valley, the municipality with the highest number of cases was São José dos Campos, with 3,560 cases, followed by Taubaté with 2,974 and Pindamonhangaba with 1,436 reports. Therefore, the epidemiological analysis of dengue in children proves essential for understanding the course of the disease and the time of year when greater awareness about its prevention becomes necessary.